Analysing employers’ expectations of employee skills in the South African tourism industry - Faith N. Zwane (South African Journal of Human Resource Management, 2014)
Orientation: Owing to the nature of the tourism industry, which is highly service orientated, employees should possess certain skills such as self-reliance, people and certain specialist skills, and general employability when working in this industry. However, it seems that employees are not well enough prepared and equipped with these skills to satisfy the requirements of employers. Thus human resource practitioners need to provide more in-service training. Furthermore, there is a high turnover of employees, which adds pressure to the management of human resources.